On the combination of gravity field time series derived from kinematic positions of Low Earth Orbiting satellites - Grombein, Thomas; Lasser, Martin; Arnold, Daniel; Meyer, Ulrich; Jäggi, Adrian (2021)
The Earth’s time-variable gravity field provides important information for the monitoring of changes in the Earth’s system. Dedicated satellite missions like GRACE and GRACE-FO use ultra-precise inter-satellite ranging observations to derive time series of monthly gravity field solutions. Alternative gravity field information can be obtained from the analysis of GPS-based kinematic orbit positions of Low Earth Orbiting (LEO) satellites. Although this technique is less sensitive, it can provide mostly uninterrupted time series, which is particularly valuable for those months where no inter-satellite ranging measurements are available from GRACE or GRACE-FO. Furthermore, the increasing number of operational LEO satellites makes it attractive to produce combined Multi-LEO gravity field solutions that will take advantage of a large number of observations and the variety of complementary orbital configurations. At the Astronomical Institute of the University of Bern (AIUB) GPS-based kinematic orbits have been generate for various LEO satellites like GRACE and GOCE or are routinely processed for operational missions like GRACE-FO, SWARM, Sentinel or Jason. In this contribution, we will use these kinematic LEO positions to perform gravity field recovery with the Celestial Mechanics Approach and to derive monthly gravity field times series. By evaluating mass trends and changes in Greenland, Antarctica and the Amazon river basin, the time series of different LEOs are compared with respect to superior solutions based on inter-satellite ranging. Finally, we will combine the gravity field solutions of different LEO satellites either on solution level using variance component estimation or on normal equation level and investigate their individual contribution and the additional value of the combination.